2021
DOI: 10.1155/2021/6683098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroxychloroquine and Azithromycin on QT Interval Prolongation and Other Cardiac Arrhythmias in COVID-19 Confirmed Patients

Abstract: Background. Hydroxychloroquine with or without azithromycin was one of the common therapies at the beginning of the COVID-19 pandemic. They can prolong QT interval, cause torsade de pointes, and lead to sudden cardiac death. We aimed to assess QT interval prolongation and its risk factors in patients who received hydroxychloroquine with or without azithromycin. Methods. This study was a retrospective cohort study. One hundred seventy-two confirmed COVID-19 patients were included in this study, hospitalized at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
0
20
2
Order By: Relevance
“…Clinical implications of the QT-prolongation, however, have conflicting data. Several studies have shown no significant difference in arrhythmogenic events and overall outcomes 92 , 93 , 94 . QTc prolongation tended to occur more often in COVID patients who had worsening renal disease and myocardial injury 95 .…”
Section: Cardiovascular Effects From Treatment/prevention Modalitiesmentioning
confidence: 99%
“…Clinical implications of the QT-prolongation, however, have conflicting data. Several studies have shown no significant difference in arrhythmogenic events and overall outcomes 92 , 93 , 94 . QTc prolongation tended to occur more often in COVID patients who had worsening renal disease and myocardial injury 95 .…”
Section: Cardiovascular Effects From Treatment/prevention Modalitiesmentioning
confidence: 99%
“…The emergence of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has resulted in many individuals becoming infected, more than four million deaths, and has placed an unprecedented burden on public health services worldwide. 1 , 2 , 3 Vaccinations against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is a crucial step in ending the current worldwide pandemic. However, several particularly vulnerable groups in the population were not included in sufficient numbers in coronavirus disease 2019 (Covid‐19) vaccine trials.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 74 articles reporting data on the safety of HCQ or CQ in patients treated for COVID-19 were found [ 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , ...…”
Section: Resultsmentioning
confidence: 99%